Candrakīrti's Madhyamakāvatārabhāṣya, Chapters 1 to 5. - Lasic, Horst (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
This book contains a critical Sanskrit edition of the first fivechapters of the Madhyamakāvatārabhāṣya, a work that presents the steps of the path to full Awakening according to the "GreatVehicle" of Buddhism. The author of the work, the Indian scholar Candrakīrti (circa A.D. 570-650), is one of the most important representatives of the Madhyamaka, the "Middle Way," school-one of the two main schools of the Great Vehicle-which wasfounded by Nāgārjuna in the second or third century.